Translating worlds: migration, memory and culture, by Radstone, S. & Wilson, R. (eds. - Osório Cardoso, Maria Ivone (2022)
This volume,edited by Susannah Radstone and Rita Wilson, explores the relations betweentranslation, migration and memory,froman international and interdisciplinary perspective. It brings together humanities-oriented researchersfrom a range of related academic disciplinesto take part in the translation process,as a means of communication, re-narration, trans-creationand localization across a varietyof domains. Translation is therefore extended beyond the mere comprehension of one language byanother. Italso encompassescomplex andmulti-layeredprocesses,that areactive, inevitable, yet malleable,having an intrinsic place and space in society, mixing the old and the new, the familiar and the unknown brought into conversation and connection.That is why the book deals with“translating worlds”, rather than translatingwords.In this sense, the pastis prolongedtothe present and historical moments inform the contemporarytime. These acts of interpretation, mediation, and negotiation constantly take place across cultures, through visual, vocal, aural, written, analogue or digital technologies. So, as Susannah Radstone points out in “The lost clock: remembering and translating enigmatic messages from migrant objects”,it is a livingportrait of a global world with unprecedentedmovements of people(s), mobilityof cultures and migration of other worldviews.